ANALISIS SEKTOR PARIWISATA SEBELUM DAN SESUDAH PANDEMI COVID 19 DILIHAT DARI JUMLAH TAMU HOTEL DI PROVINSI JAMBI - Agus Santoso; Trie Hierdawati; Rian Dani (Journal Of Business, Finance, and Economics (JBFE), 2023)
The purpose of the first research on the condition of the tourism sector before and after the COVID-19 pandemic seen from the number of foreign hotel guests in Jambi Province where before the pandemic in 2017 to 2018 the number of foreign hotel guests increased by 5.59% with the number of hotel guests. of 8939 people, while for the conditions during the pandemic in 2019-2020, it experienced a very sharp decline of -73.69% with the number of hotel guests of 6759 people or a decrease compared to the two years before the pandemic, which was 2180 people. The two conditions of the tourism sector before and after the covid 19 pandemic were seen from the number of hotel guests in Jambi Province before the 2017-2018 pandemic, namely an increase of 16.47% per year or an increase in 2018 the number of hotel guests in the archipelago of 423,262 people with a total before the pandemic, hotel guests were 786,662 people. Meanwhile, the condition of the tourism sector before and after the COVID- 19 pandemic, seen from the number of hotel guests in Jambi Province during the pandemic, actually experienced a shock, namely in 2020 up to -38.08%.